Self-Esteem and Social Anxiety Among Generation Z Social Media Users: a Literature Review - Arifatul Husna; Yufiarti; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Generation Z’s attachement to social media affects various psychological aspects, particularly in terms of self-esteem and social anxiety. Various types of content are shared on social media, often with the aim of attracting attention and gaining validation from other users. The purpose of this literature review is to synthesize and analyze relevant studies that discuss how social media influences self-esteem and social anxiety. The literature review was conducted by analyzing 20 articles published between 2018 – 2025. The articles are related to the impact of social media on self-esteem and social anxiety among Generation Z social media users and were searched using the Google Scholar, Scopus AI, and Sciencedirect databases. The review found that social media use has a significant and complex impact on self-esteem and social anxiety among Generation Z. Key triggers may stem from social comparison, Fear of Missing Out, and demographic factors.